THE EFFECT OF IMPLEMENTATION OF POPULATION ADMINISTRATION POLICY AND EMPLOYEE MOTIVATION ON QUALITY OF SERVICE AND ITS IMPACT ON COMMUNITY SATISFACTION IN ISSUANCE OF BIRTH ACCESS (Case in : The Department of Population and Civil Registration of the Dharm - Fatra, Ade; Heryanto, Heryanto (Archives of Business Research, 2019)
This study tries to examine the effect of policy implementation and employe motivation towards Quality of Service and its impact on Community Satisfaction in publishing a Birth Certificate at the Department of population and civil registration in Dharmasraya Regency. The purpose of this study is to examine the effect of variable policy implementation and motivation on service quality variables and community satisfaction. This study uses descriptive quantitative methods. The study population consisted of 100 people from the community and 55 people from employees. To obtain valid and realistic instruments, the validity and reliability test, normality test, multicollinearity test and heteroscedasticity test were tested. The data analysis technique used is linear regression analysis, t test, f test, determination coefficient, and path analysis using the SPSS program, with α = 0.05.The results showed that Policy Implementation had a positive and significant effect on community satisfaction both partially and simultaneously, as well as the Quality of Service as an intervening variable capable of providing increased influence on community satisfaction. Whereas motivation does not have an influence on Service Quality and Community satisfaction. The empirical findings indicate that in order to increase Community Satisfaction, the Dharmasraya District Population and Civil Registration Office needs to pay attention and focus more on improving the factors of Policy Implementation and Service Quality.